Survey Of Total Microbes And Molds In Avocado Juice In Sukolilo District, Surabaya - Rizki, Yulia Rizki; Handarini , Kejora; Rahmiaty, Retnani (Universitas Dr Soetomo, 2024)
Fresh avocado juice is a very popular drink, but it carries the risk of microbial contamination if it is handled with little attention to hygiene and sanitation. The high total number of microbes and yeasts in food that exceeds SNI provisions indicates that the food product is rotten and is not suitable for consumption. High total microbial contamination can be a sign of the presence of pathogenic microbes. This research aims to determine the total microbial and yeast contamination content found in avocado juice in Sukolilo District, Surabaya. This research uses a descriptive method by taking samples from all avocado juice traders in Sukolilo District, Surabaya. The parameters tested were total microbes, total yeast mold and hygiene and sanitation observations of juice traders (ingredients, processes, workers) as supporting parameters. The results of the research showed that the total microbes in avocado juice in Sukolilo District ranged from 3.2 x 102 CFU/ml to 9.9 x 104 CFU/ml, there were 65.22% of samples exceeding the limit determined by SNI (1.0 x 104 CFU/ml). The total mold-yeast ranged between 8.20 x 103 CFU/ml and the highest was 1.07 x 105 CFU/ml, there were 100% of samples exceeding the limit determined by SNI (1.0x102 CFU/ml). Seller's hygiene is not paid attention to, such as not wearing aprons, gloves, head coverings, and not washing hands when making juice. Sanitation is also not paid attention to, including: the fruit used is of poor quality and is kept at room temperature during serving, the blender is not washed with detergent, the refilled water is used to make juice